Answer :

Answer:

You got it wrong.  It is supposed to be (1, -4)

Step-by-step explanation:

If you are not sure, just plug it in.  So based on this you got that x= -6.

So plug x=-6 into the first equation.  -6= -y-3.  So you solve for y.

You add 3 to both sides and get that -3= -y and y=3, so you did not get it correct because you got that y=-4.  So you may be asking, how do you do this?

So first, you already know that x=-y-3.  So you substitute that into the 2nd equation for x.  That gets you -2(-y-3)-y=2.  Use distributive property and get 2y+6-y=2.  Combine like terms and subtract 6 from both sides to get y= -4.

 

Now you substitute y=-4 into any equation, I'll just use the first equation.  X= -(-4)-3.  That gets x= 4-3.  That gets x= 1

Other Questions